A Model Predictive Controller for the Core Power Control System of a Lead-Cooled Fast Reactor - Hu, Yang; Liang, Lehua; Chen, Lekang; Zeng, Wenjie (Frontiers in Energy Research, 2022)
In this paper, to study the model predictive control (MPC) for core power control system of lead-cooled fast reactor (LFR), based on the state space model of LFR core, a model predictive controller is used to the core power control system. The conditions of 20pcm step reactivity and 5% step down of coolant inlet temperature are introduced to study the control characteristic, the Maximum Overshot (MO) and the transient time are calculated in time domain, and the stability of core power control system is analyzed by Nyquist diagram and Bode diagram. The result show that the control effect of core power control system with MPC controller is better than the core power control system with PID controller, and both of them are closed loop stable system.